Medial epicondylitis in pitchers of La Isla de la Juventud - Yidier Pons Gámez; Yoanni Gil López; Humberto Durañona Nápoles; Wilfredo Lorenzo Romero (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
Tendinopathy is a major cause of musculoskeletal morbidity. A high incidence of sports-related injuries of 30-50% in professional and recreational athletes, which can compromise sports performance and cause disability. Mostly, it is caused by an alteration in the muscle-tendontium origins in the humeral condyles. In most cases, it is in the working population, so it has a high impact on reducing productivity due to absences from work, which, depending on the severity, can range from days to weeks. The general objective of the research is to propose a complex of physical exercises that will contribute to the recovery of such injury in baseball pitchers. Theoretical and empirical methods were used and the theoretical foundations for the rehabilitation of medial epicondylitis were determined. The information obtained after interviewing the coaches was analyzed in order to characterize the current state of the rehabilitation process for this injury. Based on the results obtained, a set of physical exercises was designed to rehabilitate this injury in the training area. The exercises designed are classified into passive, assisted active, free active, and resisted active; the latter being divided into two groups. In order to facilitate the work of the trainers, the form of execution of the exercises is described, as well as the methodological indications, muscles involved, organization and variants.